An analytical approach to predict cohesion and interfacial failures of CFRP/steel composites under prolonged exposure to aqueous solutions. (June 2022) - Perera, U.N.D.; Kahandawa Arachchi, K.A.D.Y.T.; Gamage, J.C.P.H.
Abstract: The long-term performance of Carbon Fibre Reinforced Polymer (CFRP) strengthened steel joint under prolonged exposure to moisture conditions is imperative in the applications of structures exposed to groundwater or seawater. Analytical models to determine the bond characteristics of CFRP/steel composites subjected to prolonged exposure in aqueous solutions are yet to be explored. This paper explores the cohesive and interfacial failure parameters of such CFRP/Steel composites theoretically. Thirty double-strap joints and twenty adhesive coupons were tested to determine the residual strength after exposure to seawater and distilled water for 6 and 12 months. An analytical model was developed to determine the degradation of adhesive material, bond and the interfaces of composite exposed to seawater and distilled water. The developed model is in good agreement with test results and capable of predicting initial bond degradation rate and stabilized degradation under-considered exposure conditions. Furthermore, the model could predict the contribution from the interfaces, bond line, and adhesive component on the degradation of composite in service. Highlights: Prolonged immersion in distilled water (DW), seawater (SW) and dry/wet exposure to SW conditions were considered. A theoretical model was developed using the concept in the Hart-Smith model to predict the long-term bond characteristics. A 63% degradation of bond strength was noted when exposed to dry/wet SW conditions. The theoretical model developed can be used to attain the required CFRP bond length and long-term performance effectively.